YIDDISH PREFIXED VERBS WITH AVEK-: A COGNITIVE SEMANTIC CLASSIFICATION - K. A. Shishigin (Вестник Кемеровского государственного университета, 2013)
This article introduces a cognitive-semantic classification of Yiddish prefixed verbs with avek-. It takes into account the spatial etymology of the prefix and considers the prefixed verbs from the standpoint of the semes acquired by virtue of the prefixation and from the standpoint of the described situation and situation concept.